PERFORMANCE OF THE LM 386 SOUND SENSOR IN DETECTING FRUIT MATURITY BASED ON SOUND FREQUENCY - Kurnia Paranita Kartika Riyanti (Universitas Islam Balitar, 2018)
The LM 386 module is a sensor that is used to detect sound frequencies. This module consists of amplifiers with low power audio frequencies, has an internal resistor of 135K Between feet 1 and 8 feet. In this study a test of the ability of the LM 386 sensor was carried out in capturing the sound vibrations produced by watermelon. This is done to facilitate the watermelon traders in determining the maturity level of the watermelon that will be sold to consumers. The working principle of this tool is to capture the sound vibrations of the watermelon launched on the media, then the sound vibrations of the watermelon will be displayed on the ADC. Then the buzzer is added to the device to detect certain ADC values ​​that indicate mature watermelon and are ready to be sold to consumers. The indication of ripe watermelon is a buzzer sound and an indication of immature watermelon has no buzzer. From the results of this study it is known that for mature and immature watermelon, the ADC reading value is not much different. The mature watermelon value is 26-28 ADC, while the immature watermelon the ADC value produced is 19-25. For raw watermelon the ADC value that is produced is 30-35. Functionally this sensor can work well, but there are still weaknesses in terms of sensor sensitivity. LM 386 is less sensitive in detecting the exact value of mature and immature watermelons. Lm 386 sensor is more sensitive in detecting the type of sound in the form of a blow.